Transformasi Digital Layanan Publik di Kota Batam: Tantangan dan Peluang Menuju Tata Kelola Berkelanjutan - Rifqi Mei Redha, Moch; Agus Sumarno, Dwi; Alimudin, Aidil (Prodi Ilmu Administrasi Negara, 2025)
This study explores the dynamics of digital transformation in Batam’s public service delivery, with a focus on four key dimensions: robust digital infrastructure, data-driven decision-making, enhanced cybersecurity, and citizen-centric service design. Using a qualitative descriptive approach supported by policy analysis and empirical data from government reports, media sources, and international studies, the research highlights both opportunities and challenges in realizing sustainable governance. The findings reveal significant progress, including the implementation of the Matrix Cable System, the development of the Online Single Submission (OSS) system, and the integration of more than 400 services in the Batam Public Service Mall (MPP). However, challenges persist, such as limited cross-sectoral collaboration in infrastructure development, low data literacy among civil servants, high cybersecurity risks, and uneven digital literacy within society. The study concludes that sustainable digital governance in Batam requires not only technological investment but also institutional strengthening, human capital development, and active citizen engagement. These insights contribute to the broader discourse on how local governments in developing countries can balance innovation and inclusivity in digital transformation pathways